Menstruation: gap in knowledge, belief and practice among adolescent girls in an urban area of Belagavi - Kanyadi, Suhasini; Metgud, Chandra S. (International Journal Of Community Medicine And Public Health, 2017)
Background: The period of adolescence, beginning with the onset of puberty, is a crucial transition into adulthood. There is a substantial lacuna in the knowledge, belief and practice about menstruation. This study addresses the gap in knowledge, belief and practice regarding menstruation among adolescent girls. Methods: A community based cross sectional study was conducted over a period of one year, in an urban area of Belagavi among 625 adolescent girls in the age group of 16–19 years. Data was collected by house to house visit using a predesigned, pretested questionnaire. Results: The mean age (±SD) at menarche was found to be 12.8±1.73 years. Our study showed that as the knowledge increased, there was increase in the use of sanitary pad (p<0.001) and increase in the number of girls practicing cleaning of external genitalia during menstruation (p<0.01). However, it was found that 276 (50.5%) and 175 (37.7%) of the girls did not use sanitary pads and practice cleaning of external genitalia during menstruation even after having correct knowledge showing a gap in knowledge and practice. Similarly, among the 494 girls who knew that menstruation is a natural process, 93 (18.8%) girls wrongly believed she shouldn’t sleep in the same place as usual, 124 (25.1%) said she shouldn’t enter the kitchen, 186 (37.7%) believed that certain foods should be avoided and only 37 (7.5%) rightly believed that girls could go to place of worship during menstruation showing a gap in knowledge and belief. Conclusions: The study reported a gap in knowledge, belief and practice among adolescent girls. To bridge this gap causes have to be identified and addressed.